Analisis Rasio Keuangan terhadap profitabilitas pada perusahaan Transportasi Umum Yang Terdaftar di BEI 2014-2015 - Siti Khoirina; Ade Frisilia Febriyani (Universitas Mitra Indonesia, 2021)
This research aims to analyze the influence of financialratio to measurethelevelof profitability with well partiallyor simultan. Financial ratioinclude Current Ratio This research is using purposive sampling techniqueto collect data population from financial reports 2014-2017 The analysis of data used descriptive statistics,classic assumptiontest, multiple regressionanalysis, hypothesis testing mand analysis of the coefficient of determination (R2). The results of this research showed that aspartially variable Current ratio has significant influence to the Profitability,and variable Debt to equity ratio, and Total asset turn over.doesn’t have influence to Profitability, and variable NIM have dominant influence to the Profitability. While simultane ously variable Current ratio has significant influence on Profitability. Based on the results of value 47,3% of coefficient of determination(R2),all independent variables have strong influence in Explaining the dependent variable. Keywords: Current ratio, Debt to equity ratio, Total asset turn over dan Profitability